Antithrombin Dublin (p.Val30Glu): a relatively common variant with moderate thrombosis risk of causing transient antithrombin deficiency - Navarro-Fernández, José; Morena-Barrio, María Eugenia de la; Padilla, José; Miñano, Antonia; Bohdan, Nataliya; Águila, Sonia; Martínez-Martínez, Irene; Sevivas, Teresa S.; de Cos, Carmen; Fernández-Mosteirín, Nuria; Llamas, Pilar; Asenjo, Susana; Medina, Pilar; Souto, Juan Carlos; Overvad, Kim; Kristensen, Søren R.; Corra, Javier; Vicente, Vicente (Thrombosis and Haemostasis, 2016)
The key haemostatic role of antithrombin and the risk of thrombosis associated with its deficiency support that the low incidence of antithrombin deficiency among patients with thrombosis might be explained by underestimation of this disorder. It was our aim to identify mutations in SERPINC1 causing transient antithrombin deficiency. SERPINC1 was sequenced in 214 cases with a positive test for antithrombin deficiency, including 67 with no deficiency in the sample delivered to our laboratory. The p.Val30Glu mutation (Antithrombin Dublin) was identified in five out of these 67 cases, as well as in three out of 127 cases with other SERPINC1 mutations. Genotyping in 1593 patients with venous thrombosis and 2592 controls from two populations, revealed a low prevalent polymorphism (0.3 %) that moderately increased the risk of venous thrombosis (OR: 2.9; 95 % CI: 1.07–8.09; p= 0.03) and identified one homozygous patient with an early thrombotic event. Carriers had normal anti-FXa activity, and plasma antithrombin was not sensitive to heat stress or proteolytic cleavage. Analysis of one sample with transient deficit revealed a type I deficiency, without aberrant or increased latent forms. The recombinant variant, which lacked the two amino-terminal residues, had reduced secretion from HEK-EBNA cells, formed hyperstable disulphidelinked polymers, and had negligible activity. In conclusion, p.Val30Glu by affecting the cleavage of antithrombin’s signal peptide, results in a mature protein lacking the N-terminal dipeptide with no functional consequences in normal conditions, but that increases the sensitivity to be folded intracellularly into polymers, facilitating transient antithrombin deficiency and the subsequent risk of thrombosis.
Keywords: Antithrombin; deficiency; polymorphism; SERPINC1; thrombophilia